2009
DOI: 10.3109/03602530903219220
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endobiotics glucuronidation by ligand-activated transcription factors: physiological function and therapeutic potential

Abstract: Recent progresses in molecular pharmacology approaches have allowed the identification and characterization of a series of nuclear receptors (NR) which efficiently control the level UDP-glucuronosyltransferase (UGT) genes expression. These regulatory processes ensure optimized UGT expression in response to specific endogenous and/or exogenous stimuli. Interestingly, numerous endogenous activators of these NRs are conjugated by the UGT enzymes they regulate. In such a case, the NR-dependent regulation of UGT ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 107 publications
1
16
0
Order By: Relevance
“…We thus checked whether the expression and activity of UGTs in the small intestine are elevated. The hepatic expression of Ugts has been previously been shown to play an important role in the metabolic elimination of bile acids202122. However, very little is known about the role of intestinal UGTs in determining the homeostasis of bile acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus checked whether the expression and activity of UGTs in the small intestine are elevated. The hepatic expression of Ugts has been previously been shown to play an important role in the metabolic elimination of bile acids202122. However, very little is known about the role of intestinal UGTs in determining the homeostasis of bile acids.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, these results strongly indicate that the glucuronidation of bile acids in colitis mice is drastically increased, which may explain the reduced intracellular levels of uncojungated bile acids. Unlike taurine- and glycine-conjugated bile acids, glucuronidated bile acids cannot be reabsorbed and may represent an important detoxification mechanism under the condition of abnormal bile acids accumulation21. Previous studies suggested that the hepatic glucuronidation of bile acids may be part of a negative feedback mechanism by which bile acids limit their biological activity and control their intracellular level to avoid a pathophysiological accumulation2340.…”
Section: Discussionmentioning
confidence: 99%
“…Among the human UGT1A and UGT2B, UGT1A3, UGT2B4, and UGT2B7 have a capacity to convert BAs into BA glucuronides (BA-G) in vitro. UGT1A3 is the major enzyme for hepatic production of BA-24G, and UGT2B4 and UGT2B7 are the main producers of ether glucuronides (Pillot et al, 1993;Gall et al, 1999;Trottier et al, 2006;Court et al, 2008;Verreault et al, 2010). We compared the activity of UGT2A enzymes UGT2A1 and UGT2A2 Glucuronidate Bile Acids in conjugating six BA species found as glucuronide derivatives in the human blood (Trottier et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Glucuronide conjugates represent up to 10% of the BA circulating pool in healthy volunteers (Trottier et al, 2012), and their formation involves either the 3/6-hydroxyl or 24-carboxyl group of the BA steroid nucleus for the respective formation of ether 3/6G or acyl/ester 24G (Gall et al, 1999;Caron et al, 2006;Trottier et al, 2006Trottier et al, , 2012Court et al, 2008;Verreault et al, 2010). Among the human UGT1A and UGT2B, UGT1A3, UGT2B4, and UGT2B7 have a capacity to convert BAs into BA glucuronides (BA-G) in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Because DHEAS and PREGS are also major excitatory neurosteroids, these ob- Bile acids can signal to the cell via two major receptors, the nuclear receptor FXR, and GPBAR-1/TGR5 [17][18][19][20][21][22][23] . The latter is a membrane-bound G-protein-coupled receptor that can mediate the rapid, transcription-independent actions of bile acids.…”
Section: In Addition To Bile Acids Ost ␣ -Ost ␤ Mediates the Transpomentioning
confidence: 99%